2008
DOI: 10.1128/jvi.00423-08
|View full text |Cite
|
Sign up to set email alerts
|

Small Capsid Protein pORF65 Is Essential for Assembly of Kaposi's Sarcoma-Associated Herpesvirus Capsids

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) is the etiologic agent for KS tumors, multicentric Castleman's disease, and primary effusion lymphomas. Like other herpesvirus capsids, the KSHV capsid is an icosahedral structure composed of six proteins. The capsid shell is made up of the major capsid protein, two triplex proteins, and the small capsid protein. The scaffold protein and the protease occupy the internal space. The assembly of KSHV capsids is thought to occur in a manner similar to that determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 55 publications
1
59
0
Order By: Relevance
“…Therefore, in contrast to the suggested essential role of SCP in the in vitro assembly studies, KSHV SCP is not essential for capsid assembly in vivo, but rather dramatically enhances the efficiency of capsid assembly. It is also possible that capsids were also assembled in the absence of SCP in previous in vitro studies but might have eluded detection as a result of their scarcity (16,38). Our structure and in vivo mutagenesis studies support the notion that SCP is nonessential and plays a secondary or auxiliary role.…”
Section: Structure-guided Mutagenesis Establishes Scp's Auxiliary Rolsupporting
confidence: 71%
See 2 more Smart Citations
“…Therefore, in contrast to the suggested essential role of SCP in the in vitro assembly studies, KSHV SCP is not essential for capsid assembly in vivo, but rather dramatically enhances the efficiency of capsid assembly. It is also possible that capsids were also assembled in the absence of SCP in previous in vitro studies but might have eluded detection as a result of their scarcity (16,38). Our structure and in vivo mutagenesis studies support the notion that SCP is nonessential and plays a secondary or auxiliary role.…”
Section: Structure-guided Mutagenesis Establishes Scp's Auxiliary Rolsupporting
confidence: 71%
“…The aforementioned cross-linking of hexon MCPs by SCPs suggests that SCP may function by strengthening the integrity of hexons in the capsid. In this regard, previous studies with recombinant capsid proteins in a baculovirus expression system have suggested an essential role of SCP in KSHV and EBV in vitro capsid assembly (16,17), and the "essential" region of SCP was further mapped to the N-terminal half by mutagenesis scan with the in vitro capsid assembly system (17,38). To assess whether SCP is also essential for in vivo viral assembly and to better understand its mechanism of action, we performed conventional transmission EM of mutant virus-infected cells and cryoEM of purified viruses bearing SCP-null mutation or SCP C-terminal truncation.…”
Section: Structure-guided Mutagenesis Establishes Scp's Auxiliary Rolmentioning
confidence: 99%
See 1 more Smart Citation
“…Although its homologues are nonessential in Alphaherpesvirinae and Betaherpesvirinae, it has recently been shown to be required for KSHV capsid formation (43). On the basis of full occupancy, it should be the second most abundant capsid protein.…”
Section: Discussionmentioning
confidence: 99%
“…Spodoptera frugiperda (Sf9 and Sf21) cells were grown in Grace's insect cell medium, supplemented with 10% fetal calf serum (Gibco-Invitrogen). Sf9 and Sf21 cells were propagated as described by Perkins et al (37) and Okoye et al (38). Baculoviruses were made using the BAC-to-BAC system from Invitrogen.…”
Section: Methodsmentioning
confidence: 99%